Blot hybridisation analysis of genomic DNA. Issue 3 (June 1984) - Vandenplas, S; Wiid, I; Grobler-Rabie, A; Brebner, K; Ricketts, M; Wållis, G; Bester, A; Boyd, C; Måthew, C
Abstract : Restriction endonuclease analysis of specific gene sequences is proving to be a valuable technique for characterisation and diagnosis of inherited disorders. This paper describes detailed protocols for isolation, restriction, and blot hybridisation of genomic DNA. Problems and alternatives in the procedure are discussed and a troubleshooting guide has been provided to help rectify faults.